2017
DOI: 10.1111/jnc.13911
|View full text |Cite
|
Sign up to set email alerts
|

Dual specificity phosphatase 15 regulates Erk activation in Schwann cells

Abstract: Schwann cells and oligodendrocytes are the myelinating cells of the peripheral and central nervous system, respectively. Despite having different myelin components and different transcription factors driving their terminal differentiation there are shared molecular mechanisms between the two. Sox10 is one common transcription factor required for several steps in development of myelinating glia. However, other factors are divergent as Schwann cells need the transcription factor Egr2/Krox20 and oligodendrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Importantly, they demonstrated that sustained activation of the Ras/Raf/Erk pathway in myelinated dorsal root ganglion (DRG) neuron-SC co-cultures induces demyelination even in the presence of normal axon signaling. Consistent with this idea, another paper reported that the dual specificity phosphatase 15 (Dusp15) is necessary for full activation of Erk and that its activation represses the expression of several myelin genes including MBP (Rodríguez-Molina et al, 2017 ). While high and sustained activation of Ras/Raf/Erk signaling seems essential for SC plasticity, Ras over-activation might also be deleterious and lead to the development of SC-derived tumors in neurofibromatosis type 1 patients (Harrisingh et al, 2004 ).…”
Section: Molecular Mechanisms That Modulate Schwann Cell Plasticitymentioning
confidence: 87%
“…Importantly, they demonstrated that sustained activation of the Ras/Raf/Erk pathway in myelinated dorsal root ganglion (DRG) neuron-SC co-cultures induces demyelination even in the presence of normal axon signaling. Consistent with this idea, another paper reported that the dual specificity phosphatase 15 (Dusp15) is necessary for full activation of Erk and that its activation represses the expression of several myelin genes including MBP (Rodríguez-Molina et al, 2017 ). While high and sustained activation of Ras/Raf/Erk signaling seems essential for SC plasticity, Ras over-activation might also be deleterious and lead to the development of SC-derived tumors in neurofibromatosis type 1 patients (Harrisingh et al, 2004 ).…”
Section: Molecular Mechanisms That Modulate Schwann Cell Plasticitymentioning
confidence: 87%
“…As a key regulator for oligodendrocyte differentiation and myelin production, the DUSP15 gene plays an important role in the development and function of the nervous system [ 32 ]. The rs3746599 SNP in the DUSP15 gene was predicted to be within the conserved transcription factor binding site and thus influence the binding ability of transcription factors and, consequentially.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, signal transduction through ERK is involved in the development of SCs, including proliferation, differentiation, and myelination. [52][53][54] However, the in SCs results in hypermyelination as well as a decrease in regenerative axons and loose density of intraepithelial nerve fibers. 55,56 Thus, the investigations to uncover the mechanism by which FBLN5 regulates ERK activation, and particularly to explore role of FBLN5 in the ERK-dependent recovery of impaired SCs will be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ERK activity is dependent on the concentration of recombinant FBLN5 (Supplementary Figure 3), we have postulated that ERK activation is critical for the FBLN5‐mediated development of SCs, including proliferation and myelination. Indeed, signal transduction through ERK is involved in the development of SCs, including proliferation, differentiation, and myelination 52‐54 . However, the involvement of ERK signaling in the myelination processes of SCs is complex.…”
Section: Discussionmentioning
confidence: 99%